Back-stepping speed control for internal combustion engines. (9th July 2019) - Hong, Munan; Yao, Zhenhui; Su, Ling; Liu, Bo; Zhou, Anjian
Back-stepping technique and Lyapunov theory are employed to design an engine speed controller which can deal with unknown load torque and uncertain model parameters. The nonlinear dynamic system is presented based on a mean value engine model. A back-stepping speed controller is proposed in such a way that the intake pressure is chosen as the virtual control variable. An adaption law is then constructed to estimate the load torque online. The convergence of the proposed controller and the load torque estimator is obtained through the stability analysis based on Lyapunov theory. Simulations are conducted and the results are shown to demonstrate the controller.